Combined specular and off‐specular reflectometry: elucidating the complex structure of soft buried interfaces. Issue 3 (31st May 2021) - Hafner, Aljoša; Gutfreund, Philipp; Toperverg, Boris P.; Jones, Andrew O. F.; de Silva, Johann P.; Wildes, Andrew; Fischer, Henry E.; Geoghegan, Mark; Sferrazza, Michele
Abstract : A combined specular and off‐specular neutron reflectometry analysis algorithm on an absolute scale is presented. Experimental data from thermally annealed immiscible polymer bilayer systems are fitted. Abstract : Neutron specular reflectometry (SR) and off‐specular scattering (OSS) are nondestructive techniques which, through deuteration, give a high contrast even among chemically identical species and are therefore highly suitable for investigations of soft‐matter thin films. Through a combination of these two techniques, the former yielding a density profile in the direction normal to the sample surface and the latter yielding a depth‐resolved in‐plane lateral structure, one can obtain quite detailed information on buried morphology on length scales ranging from the order of ångströms to ∼10 µm. This is illustrated via quantitative evaluation of data on SR and OSS collected in time‐of‐flight (ToF) measurements of a set of films composed of immiscible polymer layers, protonated poly(methyl methacrylate) and deuterated polystyrene, undergoing a decomposition process upon annealing. Joint SR and OSS data analysis was performed by the use of a quick and robust originally developed algorithm including a common absolute‐scale normalization of both types of scattering, which are intricately linked, constraining the model to a high degree. This, particularly, makes it possible to distinguish readily between different dewetting scenarios driven either by the nucleation and growth of defects (holes, protrusions etc. ) or by thermal fluctuations in the buried interface between layers. Finally, the 2D OSS maps of particular cases are presented in different spaces and qualitative differences are explained, allowing also the qualitative differentiation of the in‐plane structure of long‐range order, the correlated roughness and bulk defects by a simple inspection of the scattering maps prior to quantitative fits.